2016
DOI: 10.1186/s13756-016-0116-5
|View full text |Cite
|
Sign up to set email alerts
|

APSIC guide for prevention of Central Line Associated Bloodstream Infections (CLABSI)

Abstract: This document is an executive summary of the APSIC Guide for Prevention of Central Line Associated Bloodstream Infections (CLABSI). It describes key evidence-based care components of the Central Line Insertion and Maintenance Bundles and its implementation using the quality improvement methodology, namely the Plan-Do-Study-Act (PDSA) methodology involving multidisciplinary process and stakeholders. Monitoring of improvement over time with timely feedback to stakeholders is a key component to ensure the success… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
95
0
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(107 citation statements)
references
References 64 publications
2
95
0
10
Order By: Relevance
“…Global guidelines for the prevention of intravascular catheter-related infections [36][37][38][39] emphasize the importance of educational programs for healthcare workers and patients regarding infection protection and hand decontamination. A recently published RCT by Inchingolo et al showed that educational programs with or without port protectors substantially reduced the rate of both central line-associated bloodstream infections and central venous colonization [40].…”
Section: Venous Access Care and Infection Risksmentioning
confidence: 99%
See 2 more Smart Citations
“…Global guidelines for the prevention of intravascular catheter-related infections [36][37][38][39] emphasize the importance of educational programs for healthcare workers and patients regarding infection protection and hand decontamination. A recently published RCT by Inchingolo et al showed that educational programs with or without port protectors substantially reduced the rate of both central line-associated bloodstream infections and central venous colonization [40].…”
Section: Venous Access Care and Infection Risksmentioning
confidence: 99%
“…Results from the 3SITE study showed that the risk for catheter-related bloodstream infections or symptomatic vein thromboses in femoral sites was 3.1 times higher than in subclavian sites, and 2.1 times higher in jugular vein sites than in subclavian sites [41]. It was further recommended that an ultrasound be used to reduce the number of insertions attempts and, therefore, the chance of infection [37][38][39]. Other efforts are being investigated to further reduce infection complications, such as chlorhexidine-impregnated dressings [42][43][44], which is now also a part of recent global guidelines [37][38][39].…”
Section: Venous Access Care and Infection Risksmentioning
confidence: 99%
See 1 more Smart Citation
“…Un ejemplo de esto es la higiene de manos 11 , uso de apósito estéril transparente 12 , programas de educación establecidos en correcta instalación y mantenimiento de acceso vasculares [13][14] , uso de clorhexidina como antiséptico para la preparación de la piel [15][16][17] , uso de la barrera máxima durante la inserción y mantenimiento [18][19][20][21][22][23][24][25] , así como uso de listas de verificación (check-list) de procedimientos 26 .…”
Section: Introductionunclassified
“…In addition, several viral pandemics and annual influenza strains have originated in the Asia-Pacific region, which, together, has global implications for population health.The prevention, control, and reporting of MDROs and healthcare-associated infections (HAIs) benefit from effective data dissemination plans and harmonized surveillance systems. HAIs compromise patient safety because they are preventable and serve as a reservoir for MDROs, which are associated with excess length of hospital stay, increased antimicrobial drug exposure, and excess costs [1][2][3][4][5]. In the Asia-Pacific region, the risks of HAIs have been estimated to be 2-20 times higher than in developed countries, with up to 25% of hospitalized patients reported to have acquired infections [4].…”
mentioning
confidence: 99%